Oxygen radicals in biological systems. - Packer, Lester (Methods in enzymology ;, 1994)
Since biological tissues are unstable in an oxygen atmosphere, a great deal of effort is expended by organisms to metabolically limit or repair oxidative tissue damage. This volume of Methods in Enzymology and its companion Volume 233 present methods developed to investigate the roles of oxygen radicals and antioxidants in disease. It includes techniques and assays of the activity of biothiols in soluble systems, their interaction with lipids and proteins, and the various new thiol enzymes, such as thioltransferases, being elucidated. Antioxidant reactions and gene regulation are also included.